Characterization of soy tofu substituted with palm kernel meal (Elaeis guineensis jacq): Karakterisasi Tahu Kedelai Tersubstitusi Bungkil Inti Sawit (Elaeis guineensis jacq) - Lutfi, Mohammad; Azzahra, Fadlia; Pomuruh, Felix Kristianto; Manggau, Gemaliany Pilo; Syamsuddin, Syamsuddin; Amar, Aini Auliana; Rahmadina, Hizra Nur (JITIPARI, 2025)
Tofu is a common food made from soybeans. However, because soybeans have limitations in terms of availability, other alternative ingredients such as palm kernel meal (BIS) are needed. The purpose of this study was to determine the best concentration of palm kernel meal added to tofu making so as to reduce dependence on the use of soybeans. The study was designed using a completely randomized design with 1 factorial, namely the concentration of BIS and soybeans. The concentration variations used were: A1 (control, 100% soybean), A2 (25% BIS: 75% soybean), A3 (50% BIS: 50% soybean), and A4 (75% BIS: 25% soybean). The parameters tested were BIS crude fiber, proximate analysis and tofu organoleptic. The results showed that BIS after fermentation experienced a decrease in crude fiber from 27.25 to 18.375%. Based on the proximate analysis, the variation of 75% BIS: 25% soybean is the best concentration with the highest protein content of 45.14%. Likewise, the moisture, ash, fat and carbohydrate content obtained were 79.05; 1.00; 6.20; and 0.96%. The organoleptic showed the level of panelists' liking for color, aroma, texture and taste with the value of panelists' liking level respectively 3.11; 4.09; 3.6 and 3.96 which indicates that this product can be accepted by the community.